PENGARUH RASIO KECUKUPAN MODAL, PERTUMBUHAN KREDIT, RASIO NON PERFORMING LOAN TERHADAP NILAI PERUSAHAAN PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2018-2022 - Purnomo, M. Hari (Jurnal Gici Jurnal Keuangan dan Bisnis, 2023)
The objective of this study is to examine the effect of Capital Adequacy Ratio, Loan Growth, Non Performing Loan Ratio on Firm Value at Banks listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The Independent variables of the study consist of Capital Adequacy Ratio, Credit Growth, Non Performing Loan Ratio, while the dependent variable is Firm Value. The results showed that the Capital Adequacy Ratio had an effect on the Firm's Value, while Credit Growth, and the Non Performing Loan Ratio had no effect on the Firm's Value. All variables simultaneously affect the Firm's Value.